RETRACTED: Prospects of Bioenergy Production From Organic Waste Using Anaerobic Digestion Technology: A Mini Review - Uddin, M. N.; Siddiki, Sk. Yasir Arafat; Mofijur, M.; Djavanroodi, F.; Hazrat, M. A.; Show, Pau Loke; Ahmed, S. F.; Chu, Yu-Ming (Frontiers in Energy Research, 2021)
Anaerobic digestion (AD) from organic waste has gained worldwide attention because it offers significant environmental and economic benefits. It can reduce the local waste through recycling which will conserve resources, reduce greenhouse gas emissions, and build economic resilience in the face of an uncertain future for energy production and waste disposal. The productive use of local waste through recycling conserves resources by reducing landfill space, the whole of life impacts of landfilling, and post-closure maintenance of landfills. Turning waste into a renewable energy source will assist the decarbonisation of the economy by reducing harmful emissions and pollutants. Therefore, this mini-review aims to summarise key factors and present valuable evidence for an efficient AD process. It also presents the pros and cons of different AD process to convert organic waste along with the reactor technologies. Besides, this paper highlights the challenges and the future perspective of the AD process. However, it is highlighted that for an effective and efficient AD process, appropriate temperature, pH, strong inoculum to substrate ratio, good mixing and small particle sizes are important factors. The selection of suitable AD process and reactor is important because not all types of processes and reactors are not effective for processing organic waste. This study is of great importance for ongoing work on renewable energy generation from waste and provides important knowledge of innovative waste processing. Finally, it is recommended that the government should increase their support towards the AD technology and consider the unutilized significant potential of gaseous biofuel production.